Experience of the Eliava Institute in bacteriophage therapy - Kutateladze, Mzia (Virologica Sinica, 2015)
<正>The rapid propagation of multidrug resistant bacterial strains is leading to renewed interest in bacteriophage therapy.With challenges in the treatment of bacterial infections,it is essential for people worldwide to understand how alternative approaches,such as bacteriophages,could be used to combat antibiotic resistant bacteria.The Eliava Institute